DOKTRIN PEMPIDANAAN DAN VIKTIMOLOGI DALAM DELIK ASUSILA KORBAN ANAK VERSUS PELAKU ANAK DAN DEWASA - Subiyanto, Imam (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This research identifies problems regarding what customary protection is available for children who are the target of acts of moral injustice, what obstacles exist in providing customary protection for children who are the target of acts of moral injustice, and what efforts can be made to overcome these obstacles. -those obstacles. This research aims to discover what obstacles exist in providing customary protection for children through a victimology approach, who the targets of acts of moral injustice are, and what efforts can be made to overcome these obstacles. The results of the research show that through a victimology approach, economic factors, the environment, and lack of parental supervision are the most critical factors in the occurrence of appropriate criminal behavior toward children. Traditional attention to the target objects of injustice in the tyrannical justice system has not received optimal attention, and there needs to be more public awareness of practical ways to anticipate injustice and socialize in society. Women are advised not to go out alone at night, dress neatly, and be careful not to be tempted by men